Production and Performance Evaluation of a Novel Ionic Electroactive Polymer Actuator With Ag/RGO Electrodes - Kanar, Deha Emre; Kaftelen-Odabasi, Huelya; Itik, Mehmet (Wiley, 2025)
Over the past 15 years, graphene (also known as reduced graphene oxide, RGO) with metal nanoparticle hybrid structures has garnered significant attention as a promising electrode material in electroactive polymer (EAP) actuators, owing to its high electrical conductivity, large surface area, and flexibility, which are particularly beneficial for actuators. In this paper, flexible biocompatible actuators were fabricated by hot-pressing a chitosan/ionic liquid/glycerol electrolyte layer sandwiched between two electrically conductive Ag-doped RGO electrode layers. The electrical conductivity of Ag/RGO electrodes was measured as 106.4 S/cm. The electrical conductivity values allow effective ion migration. This results in significant bending displacement of the actuator at very low applied voltages (< 4 V). As a result of the bending tests, the maximum output displacement of the Ag/RGO-CHI/IL actuator prepared by the three-step reduction method was 3.5 mm. This study highlights the role of the Ag-doped RGO electrode and chitosan electrolyte combination in improving the electrical performance and actuation response of the actuator to be flexible, lightweight, and cost effective compared to noble metal electrodes.
Keywords: Ag particle; bending performance; IPMC; RGO